2022
DOI: 10.5306/wjco.v13.i6.529
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum carcinoembryonic antigen in metastatic breast cancer patients: A prospective study

Abstract: BACKGROUND Carcinoembryonic antigen (CEA) is an important serum tumour marker with a substantial role in diagnosis and monitoring of various solid tumours. About 36%-70% of breast cancers have elevated serum CEA. And the available studies show discrepancy in addressing the prognostic significance of CEA in advanced breast cancer. AIM To estimate the serum CEA level in our metastatic breast cancer patients and correlate it with response to treatment and clinical outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The previous literatures stated that CA15-3 and CEA are two of the most widely utilized serum tumor indicators for breast cancer. Elevated levels of serum CEA are frequently observed in patients with metastatic and recurrent breast cancer [19] while the results obtained in the current work differ from previously reported articles in that the patients subjected to the study were early diagnosed and literatures regarding this stage of cancer reveled that both markers cannot be used in the deferential diagnosis due to their low sensitivity and specificity [20] which is also agreed with results obtained by Yang et al who found that elevated serum CEA levels are particularly noted in metastatic and recurrent disease [21] and Wang et al who demonstrated that serum CEA is less widely investigated as a prognostic factor than CA15-3 because of its poor sensitivity and specificity [22].…”
Section: Discussionmentioning
confidence: 99%
“…The previous literatures stated that CA15-3 and CEA are two of the most widely utilized serum tumor indicators for breast cancer. Elevated levels of serum CEA are frequently observed in patients with metastatic and recurrent breast cancer [19] while the results obtained in the current work differ from previously reported articles in that the patients subjected to the study were early diagnosed and literatures regarding this stage of cancer reveled that both markers cannot be used in the deferential diagnosis due to their low sensitivity and specificity [20] which is also agreed with results obtained by Yang et al who found that elevated serum CEA levels are particularly noted in metastatic and recurrent disease [21] and Wang et al who demonstrated that serum CEA is less widely investigated as a prognostic factor than CA15-3 because of its poor sensitivity and specificity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al's meta-analysis further supported CEA's association with larger tumor size, lymph node involvement, and advanced tumor stage [139]. Yang et al's study demonstrated that increased CEA levels during therapy could predict a poor therapeutic response [140]. However, CEA is not exclusive to breast cancer and can be elevated in other conditions, necessitating its interpretation alongside other clinical factors.…”
Section: Serological Biomarkers: the Importance Of Follow-upmentioning
confidence: 98%
“…Despite CA27.29’s greater sensitivity, its specificity compared to CA15-3 remains lower [ 180 ]. Meanwhile, the utility of CEA is questioned in metastatic breast cancer due to its elevated levels in a minor fraction of patients and a high false-positive rate among the general population, finding its primary clinical application in colorectal cancer, especially for early detection of liver metastases [ 181 , 182 ].…”
Section: Combinatorial Potential Of C-mirnas With Cfdnas and Proteins...mentioning
confidence: 99%